Extralinguistic Means Of Expressing Appeal In The Uzbek Language (Texas Journal of Philology, Culture and History, 2023)
In this article, the appearance of words such as hand, eye, eyebrow, eyelid, face, lip as an extralinguistic tool in the process of addressing is highlighted on the basis of examples.